American president policy Barak Obama in convergent with Iran toward middle east (Iraqi file as a Simple ( (Tikrit Journal For Political Science, 2024)
The administration of President Barack Obama represented the clear model of American foreign policy in dealing with Iran in a special way of change and continuity. It adopted a special approach to dealing with the necessity of dealing with the necessities of the American interest and the circumstances surrounding it politically, economically and militarily. With Iran at the same time mistakenly committed to the continuity of the US policy of conflict and the linkage between the two parties in light of the worsening problem in the United States of America Iraq. .. As a natural problem, Iraq represented a model of conflict and cooperation between the two parties under the policy of US President Barack Obama, whose priorities in Iraq marked the beginning of the US withdrawal from Iraq in the first period of Obama's rule, which led to a series of understandings through covert and overt channels for the successful withdrawal of US forces. Increasing Iranian Influence and Influence in Iraq After a crisis of daesh, the level of US-Iranian coordination has increased in order to reduce the force first and then expel it from the territories it occupied, with several tensions and mutual accusations between the parties at different periods of war